Elaboração de cervejas tipo lager a partir de farinha de pupunha (Bactris gasipaes kunth) como adjunto, em bioprocessos conduzidos com leveduras livres imobilizadas - Souza, Patrick Gomes de (2010)
Beer is an alcoholic beverage obtained by fermentation of beer wort, consisting of water, barley malt and hops. Usually they use biomass as starchy adjuncts to enrich the content of fermentable carbohydrates. Brazil is fourth in world rankings in the production of beer. In this dissertation is proposed the production of a lager beer with characteristics of the Amazon region through the use of peach palm flour, a regional fruit rich in starch, as an adjunct in the fermentation process with the use of free and calcium alginate immobilized yeast. The peach palm flour, previously characterized as their physical-chemical aspects, was subjected to cooking to be used as an adjunct in the preparation process of brewing mash. The fermentation process the wine was carried out with free and immobilized in calcium alginate brewer’s yeast. The bioprocess was monitored for temperature and physical-chemical parameters. The beers were characterized according to the physical-chemical, microbiological and sensory characteristics and showed Lager beer, being classified as alcoholic beers, clear and common. Beverages produced by the two fermentation processes showed good microbiological quality and sensory acceptability with more than 68%. The results showed that the peach palm flour is in an excellent source of fermentable carbohydrates for the preparation of beer. Palavras-chave: peach palm flour, immobilized yeast , beer